Developing An Authentic Assessment Rubric in Merdeka Curriculum Based on 21st Century learning Methods for 10th Grade Students - Cristiana, Olga; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu (STKIP AGAMA HINDU SINGARAJA, 2023)
Several schools in Indonesia have started to implement the Merdeka curriculum. This curriculum affects several systems in education, including the assessment process. Thus, the school needs to adjust to this curriculum, including the teacher and students. This study is conducted to develop an authentic assessment rubric based on the 21st century learning method in the Merdeka curriculum for assessing 10th grade senior high school students. In developing the product, the researcher uses the research method, namely Design and Development. 4 Stages must be passed in developing the product: Analysis, Design, development, and Evaluation stages. In collecting the data, 42 respondents, one English teacher and 41 students in SMAN 4 Singaraja, were involved. The data were collected with four instruments: observation, interview with the English teacher, questionnaire for students, and document analysis. Then, the data were analyzed with a mixed method. After being evaluated by several experts in 2 stages, the rubric is categorized as an excellent rubric and appropriate to be implemented by an English teacher in the English learning process.